Cytotoxic, Virucidal, and Antiviral Activity of South American Plant and Algae Extracts. (24th April 2012) - Faral-Tello, Paula; Mirazo, Santiago; Dutra, Carmelo; Pérez, Andrés; Geis-Asteggiante, Lucía; Frabasile, Sandra; Koncke, Elina; Davyt, Danilo; Cavallaro, Lucía; Heinzen, Horacio; Arbiza, Juan
Abstract : Herpes simplex virus type 1 (HSV-1) infection has a prevalence of 70% in the human population. Treatment is based on acyclovir, valacyclovir, and foscarnet, three drugs that share the same mechanism of action and of which resistant strains have been isolated from patients. In this aspect, innovative drug therapies are required. Natural products offer unlimited opportunities for the discovery of antiviral compounds. In this study, 28 extracts corresponding to 24 plant species and 4 alga species were assayed in vitro to detect antiviral activity against HSV-1. Six of the methanolic extracts inactivated viral particles by direct interaction and 14 presented antiviral activity when incubated with cells already infected. Most interesting antiviral activity values obtained are those of Limonium brasiliense, Psidium guajava, and Phyllanthus niruri, which inhibit HSV-1 replication in vitro with 50% effective concentration (EC50 ) values of 185, 118, and 60  μ g/mL, respectively. For these extracts toxicity values were calculated and therefore selectivity indexes (SI) obtained. Further characterization of the bioactive components of antiviral plants will pave the way for the discovery of new compounds against HSV-1.